Persepsi tentang Proses Pembelajaran dan Kebutuhan Mahasiswa terhadap Media Pembelajaran Berbasis Lingkungan pada Matakuliah Ilmu Lingkungan - Khairunnisa Khairunnisa; Bhakti Karyadi; Yuli Febrianti; Sipriyadi Sipriyadi (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to explore perceptions related to the learning process and students' needs for environment-based learning media in the Biology Education Study Program at PGRI Silampari University. The method used is survey research with research samples, namely students who take Environmental Science courses and lecturers of the course. The study results show that the teaching-learning process in Environmental Sciences only takes place in the classroom using E-Books and relevant materials packaged in PPT as teaching material sources due to limited time for lectures. Student perceptions and criteria for the development of learning media from lecturers refer to the packaging of learning media products that contain information related to Environmental Science with the right material objectives and concepts, are easy to understand, interactive, easy to use, contain animation and media display must be attractive. In conclusion, it is necessary to develop learning media to make the learning atmosphere more fun, interactive and exciting, one of which is through the development of Learning Blog media. Keywords: Blog, Media, Perception, Environmental Science